Xây dựng chương trình thiết kế ảnh Fractal trực quan - Huy, Nguyễn Xuân; Hoài, Nguyễn Xuân (Journal of Computer Science and Cybernetics, 2016)
Fractal geometry is considered to be one of new fields in mathematics with many applications. This paper proposes a method to build a program (called VFDESIGN) in order to help the process of designing fractal images visually on computer screens. Also, we explain how this program can help users to find out fractal codes for natural objects (to solve the inverse problem).